Análisis de la importancia de la detección temprana del trastorno del espectro autista - González Mendoza, Ilonka del Carmen (Universidad Antonio Nariño, 2021)
This documentary review presents an analysis of the importance of early detection and warning signs or signs of autism spectrum disorder, which may jeopardize the child's proper development in the first and subsequent years of life, taking into account that the existing misinformation about this condition slows down the timely intervention process that will ensure a better quality of life for the patient and even his or her parents or caregivers. Therefore, it is necessary to describe the most relevant aspects of autism and the consequences if it is not detected in time even when there are different strategies to achieve it. In addition, this project is based on various bibliographic sources where everything related to the subject is interpreted and concludes with a more certain clarity about learning more about autism, detecting and intervening in time to a child with autism.